Evaluasi Komponen Hasil dan Hasil Generasi M2 dari Generasi M1 Kacang Nagara yang Diberi Perlakuan Ethyl Methane Sulphonate (EMS) - Taran Sinatra Siregar; Raihani Wahdah; Zairin Zairin (Jurusan Agronomi, Fakultas Pertanian, Universitas Lambung Mangkurat, 2026)
Nagara beans (Vigna unguiculata sp. cylindrica) are a potential local crop from South Kalimantan that can be an alternative to soybeans, but still have limited productivity. Efforts to increase yield can be done through mutation induction using Ethyl Methane Sulphonate (EMS) to produce new genetic diversity. This study aims to evaluate the differences in yield components and yield of the M2 generation compared to the M1 generation of yellow nagara beans that have been treated with EMS. The study was conducted in the practice field of SMK-PP Negeri Banjarbaru from November 2024–May 2025 using a single-factor Randomized Block Design (RBD) with 10 combinations of EMS concentrations (0; 0.03; 0.06; and 0.09%) and soaking times (4, 6, and 8 hours), each repeated three times. The variables observed were the number of pods per plant, pod length per plant, pod width per plant, number of seeds per plant, number of seeds per pod, seed weight per plant. Data were analyzed using the Wilcoxon sign test. The results showed significant differences between M2 and M1 in pod number, pod length and width, and seed number and weight per plant. EMS treatment at concentrations of 0% to 0.03% had a positive effect on increasing yield components, while concentrations of 0.06–0.09% tended to decrease plant performance.